Age-Dependent Paraoxonase 1 (PON1) Activity and LDL Oxidation in Wistar Rats during Their Entire Lifespan - Dileep Kumar; Syed Ibrahim Rizvi (The Scientific World Journal)
Paraoxonase 1 (PON1) is an HDL bound enzyme which plays a key role in the protection of LDL and HDL from oxidation by hydrolyzing activated phospholipids and lipid peroxide products. Oxidative stress plays a crucial role in the development of atherosclerosis by oxidation of LDL. This study was conducted to determine age-dependent changes in plasma PON1 arylesterase activity and LDL oxidation in rats during their entire lifespan. 48 Wistar strain rats were grouped in six different age groups (1, 4, 8, 12, 18, and 24 months). We observe a significant (P<0.001) age-dependent decrease in plasma PON1 arylesterase activity correlating with increase in susceptibility of LDL oxidation and increase in plasma MDA level concomitantly with a significant (P<0.001) decrease in plasma radical scavenging activity after 8 months. The reduction of PON1 and free radical scavenging activity with age could have a considerable impact on the increased incidence of atherosclerosis with age. Our observation of a significant decline in PON1 activity which correlates with increased LDL oxidation after 8 months of age is an interesting observation and needs further investigation.